PENGARUH ANGKUTAN SEDIMEN DASAR (BED LOAD) TERHADAP DISTRIBUSI KECEPATAN GESEK ARAH TRANSVERSAL PADA ALIRAN SERAGAM SALURAN TERBUKA - Kironoto, Bambang Agus (Civil Engineering Forum Teknik Sipil, 2007)
In sediment transport problems, such as the initial motion of sediment particles, scouring process, degradation process, etc., the information about the wall shear velocity, u*, is often needed. How the wall shear velocity variates in transversal direction, as the function of slopes and discharges, either for flows with and without bed load transport will be studied. The wall shear velocities, u*, are evaluated using the Clauser’s method, which is based on the velocity distribution data, due to the simplicity and the accuracy of the method. Hundred and twenty five velocity distributions data with five different slopes and five different discharges are used to study the wall shear velocity in transversal direction. The results of analysis show that the Clauser’s method still remains valid, and can be used to determine the wall shear velocity in transversal direction, as long as the velocity distributions data n the near wall region still follow the logarithmic velocity distribution. Closer to the wall, the shear velocity becomes to decrease, which is not influenced by the existence of bed load transport, as well as by the variations of slopes and discharges variations.